2011
DOI: 10.1007/s10509-011-0651-8
|View full text |Cite
|
Sign up to set email alerts
|

Interacting modified Chaplygin gas in loop quantum cosmology

Abstract: We investigate the background dynamics when dark energy is coupled to dark matter in the universe described by loop quantum cosmology. We consider dark energy of the form modified Chaplygin gas. The dynamical system of equations is solved numerically and a stable scaling solution is obtained. It henceforth resolves the famous cosmic coincidence problem in modern cosmology. The statefinder parameters are also calculated to classify this dark energy model.Comment: 7 pages, 7 figures, accepted for publication in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 33 publications
0
23
1
Order By: Relevance
“…Chen et al [14] provided the parameter space for the existence of the accelerated scaling attractor in LQC with more general interacting term. When the Modified Chaplying Gas coupled to dark matter in the universe is described in the frame work LQC by Debnath et al [15] who resolved the famous cosmic coincidence problem in modern cosmology.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [14] provided the parameter space for the existence of the accelerated scaling attractor in LQC with more general interacting term. When the Modified Chaplying Gas coupled to dark matter in the universe is described in the frame work LQC by Debnath et al [15] who resolved the famous cosmic coincidence problem in modern cosmology.…”
Section: Introductionmentioning
confidence: 99%
“…Various DE models have been investigated in this gravity [40,41]. Jamil et al [42] have investigated the cosmic coincidence problem by assuming the MCG coupled to DM. It has also been found that the future singularity appearing in the standard FRW cosmology can be avoided by loop quantum effects [43].…”
Section: Sthc For Vmvcg In Loop Quantum Cosmologymentioning
confidence: 99%
“…In recent years, many DE models have been studied in the scenario of LQC [69,70]. Jamil et al [71] have explored the cosmic coincidence problem phenomenon of modern cosmology by taking a modified Chaplygin gas coupled to dark matter. Also, some authors found that the future singularity appearing in the standard FRW cosmology can be avoided by loop quantum effects [72].…”
Section: Loop Quantum Cosmology and Pilgrim Dark Energymentioning
confidence: 99%